Localization of the position of vital anatomical structures in the lateral wall of maxillary sinus during different surgical intervention using cone beam computed tomography - Hakiem Tawfieq , Ali; Ali Hasan , Haider; Abd Alrazaq Hassan , Manar; Salah Khlfi , Mohamed (Diyala Journal of Medicine, 2023)
Background: Proper information about the anatomy of the maxillary sinus is required to avoid any unexpected complications that may arise due to the close relation between the maxillary sinus and posterior superior alveolar artery. Objective: To the current study used cone beam computed tomography CBCT imaging to assess the position of the posterior superior alveolar artery (PSAA) in relationship to the alveolar ridge and the flour of maxillary sinus. Patients and Methods: A number of 95 Iraqi patients participated in this prospective study (53 females, 42 males; age range 20-49 years). From January 2021 to February 2022, attended a 2nd specialised dentistry institution in Baquba city for CBCT scanning for numerous diagnostic and management purposes. Results: According to our study, we detected the presences of artery in (83.68%) of the sample. females showed higher PSAA prevalence than men on both sides, and the difference was significant overall, Also, the existence of artery for each side and total in the intramembranous locating in females is greater than that in males, which may demonstrate that the probability of Bleeding and other side effects is higher in males, since the existence of artery in the intramembranous area in females will reduce the likelihood of traumatic injury throughout any surgical treatment. Conclusion: This research used CBCT to determine the precise location of PSAA in the Iraqi population. This data could assist in decreasing the likelihood of hemorrhage as well as other complications which may happen throughout any surgical treatment, such as dental implant placement, ridge expansion.As well as other surgical interventions in this region.